Pelatihan Pemilihan Daging Ayam Sehat Layak Konsumsi Sebagai Upaya Pencapaian SDGS di Desa Balumbang Jaya - Danang Priyambodo; Khoirul Aziz Husyairi; Gilang Ayuningtyas (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
SDGs Desa is a sustainable development role that would be included in the priority program for using the Village Fund in 2021. Based on the results of the mapping of SDGs in 12 villages around the IPB University, especially in Balumbang Jaya, Bogor, the goals of ending hunger or eliminating hunger, achieving food security, and good nutrition, and increasing sustainable agriculture (the SDGs No 2), are still lacking. Based on this situation, it is necessary to make efforts to alleviate these problems and encourage the achievement of SDG Goal No 2. Community service program, Pelatihan Pemilihan Daging Ayam Sehat Layak Konsumsi sebagai Upaya Pencapaian SDGs di Desa Balumbang Jaya, aims to provide solutions based on academic studies, challenges, or problems that people in Balumbang Jaya Village face, with a focus on the SDGs No 2 through counseling and training. The method used is a direct presentation, discussions, filling out surveys, and participatory activities through the practice of making dishes from fresh and frozen chicken meat. This community service program concludes that there is an increase in knowledge about the selection of Aman, Sehat, Utuh, Halal (ASUH) chicken meat, as well as changes in participants' perceptions about frozen chicken meat.